Modified Delphi Process for the Development of Choosing Wisely for Inflammatory Bowel Disease. Issue 6 (June 2017) - Nguyen, Geoffrey C.; Boland, Karen; Afif, Waqqas; Bressler, Brian; Jones, Jennifer L.; Weizman, Adam V.; Fowler, Sharyle; Halder, Smita; Huang, Vivian W.; Kaplan, Gilaad G.; Khanna, Reena; Murthy, Sanjay K.; et al.
Abstract : Background and Aims: The prevalence and incidence of inflammatory bowel disease (IBD) in North America is among the highest in the world and imparts substantial direct and indirect medical costs. The Choosing Wisely Campaign was launched in wide variety of medical specialties and disciplines to reduce unnecessary or harmful tests or treatment interventions. Methods: The Choosing Wisely list for IBD was developed by the Canadian IBD Network for Research and Growth in Quality Improvement (CINERGI) in collaboration with Crohn's and Colitis Canada (CCC) and the Canadian Association of Gastroenterology (CAG). Using a modified Delphi process, 5 recommendations were selected from an initial list of 30 statements at a face-to-face consensus meeting. Results: The 5 things physicians and patients should question: (1) Don't use steroids (e.g., prednisone) for maintenance therapy in IBD; (2) Don't use opioids long-term to manage abdominal pain in inflammatory bowel disease (IBD); (3) Don't unnecessarily prolong the course of intravenous corticosteroids in patients with acute severe ulcerative colitis (UC) in the absence of clinical response; (4) Don't initiate or escalate long-term medical therapies for the treatment of IBD based only on symptoms; and (5) Don't use abdominal computed tomography (CT) scan to assess IBD in the acute setting unless there is suspicion of a complication (obstruction, perforation, abscess) or a non-IBD etiology for abdominal symptoms. Conclusions: The Choosing Wisely recommendations will foster patient–physician discussions to optimize IBD therapy, reduce adverse effects from testing and treatment, and reduce medical expenditure. Abstract : Article first published online 12 May 2017.